Rice Consumption Pattern of Rural Households in East OKU and South OKU Regencies South Sumatra Province Indonesia - Asngari, Imam; Suhel, Suhel; Bashir, Abdul; Arief, Andi Nurul A.; Susanti, Era (International Journal of Economics and Financial Issues, 2020)
This study is to examine the pattern of rice consumption of rural households case study in East OKU Regency and South OKU Regency, South Sumatra Province Indonesia. South OKU Regency is a paddy production center, and South OKU Regency is a coffee plantation center, not a rice producer. This study is field research by using household expenditure of 200 head of the family collected by using questionnaires. Method of analyzing rice food consumption by using descriptive quantitative approaches and multiple logistic regression models.. The results show that rural household spending was dominated by proportional rice food consumption. Household rice food consumption has significantly influenced the price of wheat, family income, and the number of family members. Factors the price of rice, working times, and total assets have different significance on influence rice consumption in East OKU and South OKU. Keywords: household rice consumption, food price, income, work hour, and numbers of family. JEL Classifications: D11, D12, D16, Q18, R22 DOI: https://doi.org/10.32479/ijefi.9094